Numerical Prediction Of Deformations In Laser Welded Sheets Made Of X5CrNi18-10 Steel - Piekarska W.; Kubiak M.; Saternus Z.; Stano S.; Domański T. (Archives of Metallurgy and Materials, 2015)
The work concerns the numerical modelling of coupled thermal and mechanical phenomena occurring in the laser beam welding process. Commercial Abaqus FEA engineering software is adopted to numerical computations in order to perform a comprehensive analysis of thermo-mechanical phenomena. Created in Fortran programming language additional numerical subroutines are implemented into Abaqus solver, used to describe the power intensity distribution of the movable laser beam heat source. Temperature dependent thermomechanical properties of X5CrNi18-10 steel are adopted in the numerical analysis of stress and strain states. Mathematical and numerical models are verified on the basis of a comparison between selected results of computer simulations and experimental studies on butt-welded joints.